Numerical Investigation on Aerodynamic Performance of Bird’s Airfoils - Ashraf Omar (Journal of Aerospace Technology and Management, 2020)
In this work, the aerodynamic performance of four types of bird’s airfoils (eagle, stork, hawk, and albatross) at low Reynolds number and a range of angles of attack during fixed (unflapping) gliding flight was numerically investigated utilizing open-source computational fluid dynamics (CFD) code Stanford University unstructured (SU2) and K-ω Shear Stress Transport (K-ω SST) turbulence model. The flow of the simulated cases was assumed to be incompressible, viscous, and steady. For verification and comparison, a low Reynolds number man-made Eppler 193’s airfoil was simulated. The results revealed that stork has the greatest aerodynamic efficiency followed by albatross and eagle. However, at zero angle of attack, the albatross aerodynamic efficiency exceeded all the other birds by a significant amount. In terms of aerodynamics efficiency, stork’s and albatross’s airfoils performed better than Eppler 193 at angles of attack less than 8°, while at a higher angle of attack all studied birds’ airfoils performed better than Eppler 193. The effect of surface permeability was also investigated for the eagle’s airfoil where the permeable surface occupied one-third of the total airfoil surface. Permeability increased the generated lift and the aerodynamic efficiency of the eagle’s airfoil for angles of attack less than 10°. The increase reached 58% for the lift at zero angle of attack. After the specified angle, the permeability had an adverse effect on the flow which may be due to the transition to turbulent ahead of the permeable section.